Male skin color signals direct and indirect benefits in a species with biparental care. (25th November 2014) - Montoya, Bibiana; Torres, Roxana
Lay Summary: In species that require male parental care, females are expected to choose mates based on sexual traits that indicate male genetic quality and parenting ability. Accordingly, in the brown booby, males with greener gulars are better parents and their offspring grow faster and gain more body mass. Hence, gular skin color, a trait displayed during courtship, might be a good indicator of brown booby male's genetic quality and parental care. Abstract : Particularly in species with biparental care and low levels of extrapair paternity, sexual traits that honestly indicate phenotypic and genetic quality are expected. We investigated in the brown booby, Sula leucogaster, whether gular color displayed by males during courtship is related to direct or indirect benefits to females. We performed a cross-fostering experiment in order to identify the relative contribution of parental care and genetic effects on offspring condition. We found that rearing father gular color was positively related to parental care (offspring attendance and provisioning) and chick body mass increase, whereas the genetic father gular color was related to chick structural growth. Contrary to expectations, females paired to more colorful males laid smaller eggs and did not increase parental care. Interestingly, chicks from genetic mothers with more colorful gulars and chicks that hatched from larger eggs "begged" at higher rates to mothers than to fathers. Overall, the results suggest that male gular color may provide females with reliable information on mate genetic quality and parenting abilities.